14. THE SURGICAL SITE INFECTION INCIDENCE AND RISK FACTORS AT TRAUMA – ORTHOPEDICS DEPARTMENT, THU DUC CITY HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: Determine the rate of Surgical site infection (SSI) and its associated factors at Trauma – Orthopedics Department, Thu Duc City Hospital.Methods: A prospective cross-sectional study was conducted involving 689 operated patients at Trauma – Orthopedics Department, Thu Duc City Hospital during 01/2024 - 9/2024. Determine the rate of Surgical site infection and its associated factors during patients stay in the hospital and after they are discharged period.Results: The overall surgical site infection rate was 1.6%, during hospital stay was 0,4%, and after discharge was 1,2%. Patients with a hospital stay after surgery of more than 7 days had a higher rate of surgical site infection than those with a stay of 7 days or less (p
Keywords: Surgical site infection; Surgical; Healthcare Associated Infection